2002
DOI: 10.1021/es0206846
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic(III) and Arsenic(V) Reactions with Zerovalent Iron Corrosion Products

Abstract: Zerovalent iron (Fe0) has tremendous potential as a remediation material for removal of arsenic from groundwater and drinking water. This study investigates the speciation of arsenate (As(V)) and arsenite (As(III)) after reaction with two Fe0 materials, their iron oxide corrosion products, and several model iron oxides. A variety of analytical techniques were used to study the reaction products including HPLC-hydride generation atomic absorption spectrometry, X-ray diffraction, scanning electron microscopy-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

52
276
4
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(337 citation statements)
references
References 45 publications
52
276
4
5
Order By: Relevance
“…The second peak could be fit with 2.3 Fe atoms at R As-Fe = 3.32 Å and 1.1 Fe atoms at R As-Fe = 3.55 Å from the central As atom, respectively (Table S2). Similar As-Fe distances at 3.32 Å (43-45) and 3.55 Å [38,39] were previously reported, respectively. The results suggested that bidentate binuclear and monodentate mononuclear inner-sphere complex species coexisted at the Fe-Ce surface, which corresponded to an As-Fe distance of 3.32 and 3.55 Å, respectively.…”
Section: Samplesupporting
confidence: 88%
“…The second peak could be fit with 2.3 Fe atoms at R As-Fe = 3.32 Å and 1.1 Fe atoms at R As-Fe = 3.55 Å from the central As atom, respectively (Table S2). Similar As-Fe distances at 3.32 Å (43-45) and 3.55 Å [38,39] were previously reported, respectively. The results suggested that bidentate binuclear and monodentate mononuclear inner-sphere complex species coexisted at the Fe-Ce surface, which corresponded to an As-Fe distance of 3.32 and 3.55 Å, respectively.…”
Section: Samplesupporting
confidence: 88%
“…Arsenic exists in natural water predominantly as inorganic arsenate, As (V) and arsenite, As (III) [3][4][5][6][7]. Elevated concentrations of arsenic are found in groundwater in many regions around the world, which are caused by the release of arsenic from As-bearing sediments or anthropogenic sources [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many different technologies have been developed to remove arsenic from water, such as adsorption, coagulation/precipitation, ion-exchange, and so on [3,6,7]. Among them, adsorption is considered to be one of the most promising technologies for its simplicity in operation and cost-effectivity [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An acceptable norm in many countries, including India, for arsenic (expressed as total arsenic) in drinking water is 10 μg/L [1]. Various technologies practiced for arsenic removal from ground water based on various principles are namely, chemical coagulation and precipitation [2]; oxidation [3]; biological process [4]; electrocoagulation [5]; adsorption on various materials such as alumina [6], Fe or Mn oxi-hydroxides [7] or zerovalent iron corrosion products [8] etc. ; reverse osmosis [9]; membrane filtration/ nanofiltration [10]; and ion exchange [11].…”
Section: Introductionmentioning
confidence: 99%